Análisis del storytelling como estrategia de campaña en las elecciones presidenciales de Brasil, Colombia y México 2018 - Calderón Zambrano, Adriana Lilibeth (Machala, 2020)
Storytelling is a strategy used in the advertising domain that has acquired great space in the political arena generating new formats for campaigning that activate the emotions of the voters to create a link with the candidate. Elaborating these political stories requires a structure and planning that defines the leadership profile and reinforces the loyalty of its followers. The general objective of this research was to analyze the use of storytelling as a political communication strategy in Latin American Presidential Election Campaigns 2018. The specific objectives that emerged are: a) To determine the importance of the use of storytelling as a political campaign strategy. b) To analyze the use of storytelling as a strategy within the electoral campaigns for the 2018 Latin American Presidential elections and c) To analyze the impact of people in the face of the storytelling strategy applied in the 2018 Latin American Presidential elections. This research has a descriptive methodology, aimed at a qualitative case study in which the use of storytelling in Latin American electoral campaigns of the selected candidates is analyzed. For this purpose, nine communication pieces published on their official Facebook pages were analyzed. As a complement, interviews were conducted with experts in the field who also have a long history in electoral contests, and netnography was used to analyze the impact of this strategy on citizens. As a result, the candidates used the connection stories, challenge stories, creative stories, stories that guide the future, springboard stories and stories that transmit knowledge. From the above, it was evident that candidate Jair Bolsonaro directed his stories to detail the problems Brazil was going through and the solutions he proposed within his government plan. For his part, Andrés López Obrador highlights his successful experience in public office as a letter of introduction and Iván Duque, bets on stories that show a positive scenario of the future where young people are the protagonists. Among the contributions of the interviewees is that the most employed stories revolve around the life of the candidates and their proposals. It was also identified that social networks are a great tool to disseminate this strategy, but it is necessary to consider that digital illiteracy and Internet access may be obstacles to consider. It is important to mention that the digital communities registered low interaction in the support pages for the candidates, but, their interactivity turned to the official pages of the candidates that were analyzed. In conclusion, storytelling is a strategy that, if properly managed, can become a powerful tool to persuade voters that with new technologies they are increasingly informed, more dispersed, and wary of getting involved in politics. Furthermore, storytelling creates a new and creative way of doing politics, leaving aside the traditional speeches that have lost impact and influence on the electorate. Likewise, social networks are a strong means of disseminating this strategy at a low cost.
El storytelling es una estrategia empleada en el dominio publicitario que ha adquirido gran espacio en el terreno político generando nuevos formatos para hacer campañas que activa las emociones de los votantes para crear un nexo con el candidato. Elaborar estos relatos políticos requiere de una estructura y planificación que define el perfil de liderazgo y refuerza la fidelidad de sus seguidores. Esta investigación tuvo como objetivo general analizar el uso del storytelling como estrategia de comunicación política en las Campañas Electorales Presidenciales Latinoamericanas 2018. Los objetivos específicos que se desprenden son: a) Determinar la importancia del uso del storytelling como estrategia de campaña política. b) Analizar el uso del storytelling como estrategia dentro de las campañas electorales de las elecciones presidenciales Latinoamericanas 2018 y c) Analizar el impacto de las personas frente a la estrategia storytelling aplicada en las elecciones presidenciales Latinoamericanas 2018. Este trabajo de investigación posee una metodología de alcance descriptivo, direccionado a un estudio de caso de enfoque cualitativo en el que detalla el análisis del uso del storytelling en campañas electorales latinoamericanas de los candidatos seleccionados; para lo que se analizó nueve piezas comunicacionales publicadas en sus páginas oficiales de Facebook. Como complemento se efectuaron entrevistas a expertos en el tema que además cuenta con una larga trayectoria en contiendas electorales y se acudió a netnografía para analizar el impacto de esta estrategia en los ciudadanos. Como resultado se obtuvo que los candidatos utilizan los relatos conexión, relato desafío, relato creativo, historias que guían al futuro, historia trampolín e historias que transmiten conocimiento. De lo anteriormente expuesto, se evidenció que el candidato Jair Bolsonaro direccionó sus relatos a detallar los problemas que atravesaba Brasil y las soluciones que proponía dentro de su plan de gobierno. Por su parte, Andrés López Obrador resalta su exitosa experiencia en cargos públicos como carta de presentación e Iván Duque, apostó por historias que muestran un escenario positivo del futuro donde los jóvenes son los protagonistas. Dentro de las aportaciones de los entrevistados está que los relatos más empelados giran en torno a la vida de los candidatos y sus propuestas. También se identificó que las redes sociales son una gran herramienta para difundir esta estrategia, pero es necesario considerar que el analfabetismo digital y acceso a internet pueden ser obstáculos a considerar. Es importante mencionar que las comunidades digitales registraron baja interacción en las páginas de apoyo a los candidatos, pero, su interactividad se volcó a las páginas oficiales de los aspirantes que fueron analizadas. En conclusión, el storytelling es una estrategia que manejada adecuadamente puede convertirse en una herramienta poderosa para persuadir a los votantes que con las nuevas tecnologías están cada vez más informados, más dispersos y con recelo de involucrarse en la política. Además, el storytelling crea una forma novedosa y creativa de hacer política, dejando a un lado los tradicionales discursos que han perdido impacto e influencia en el electorado. Asimismo, las redes sociales son un medio fuerte para la difusión de esta estrategia a un bajo costo.
Keywords: STORYTELLING; RED SOCIAL; PERSUADIR; RED SOCIAL